Measuring Citizens’ Acceptance and Usage of E-Government Services: Applying the Technology Acceptance Model (TAM) in Egypt - Khamis, Rana (AUC Knowledge Fountain, 2023)
The significance of public services delivery has been realized by all governments worldwide. An overarching tool to enhance government productivity and enabling citizen-centric public services, especially in developed countries, has proven to be the electronic government (e-Government). While many scholars focused on the supply side of e-government, few researches studied e-government adoption from the citizens’ perspective. To contribute to filling this research gap, this study aimed at measuring the perceptions of citizens towards the adoption of e-government services in Egypt. Using Technology Acceptance Model (TAM), the main objective of this research was gaining a better understanding of the factors affecting citizens’ attitude towards the adoption of e-government. The research used a mixed-method approach, while adopting a purposive sampling including 442 internet users in Egypt. On the one hand, the findings of this research revealed that more than 70% of the respondents using e-government do perceive the digital portal as a useful and user-friendly tool which has a positive effect on the adoption of e-government. On the other hand, trust in government, insufficient legal framework as well as the lack of online integration and coordination among government authorities are key factors affecting citizens’ attitude and perceptions negatively. Finally, the recommendations of this research which include strengthening the enabling environment and raising the awareness of citizens have a direct benefit for the Egyptian government, where other developing countries that share similar status in terms of interest in digital transformation of the public sector might potentially find the study relevant and useful. Keywords: e-government, Technology Acceptance Model, Trust, Perceived Usefulness, Citizen Adoption